AN INTEGRAL TYPE COMMON FIXED POINT THEOREM IN DISLOCATED METRIC SPACE - Panthi, Dinesh (Kathmandu University Journal of Science, Engineering and Technology, 2016)
In this article, we establish a common fixed point theorem for two pairs of weakly compatible mappings with common limit range property in dislocated metric space. Mathematics Subject Classification: 47H10, 54H25 Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. 2, 2016, page: 60-70